Buckwheat Hull Extracts Inhibit Aspergillus flavus Growth and AFB1 Biosynthesis - Nobili, Chiara; De Acutis, Agnese; Reverberi, Massimo; Bello, Cristiano; Leone, Gian Paolo; Palumbo, Domenico; Natella, Fausta; Procacci, Silvia; Zjalic, Slaven; Brunori, Andrea (Frontiers in Microbiology, 2019)
Fungal contamination poses at risk the whole food production chain - from farm to fork - with potential negative impact on human health. So far, the insurgence of pathogens has been restrained by the use of chemical compounds, whose residues have gradually accumulated determining toxic effects in the environment. Modern innovative techniques imply the use of natural and eco-sustainable bioactive plant molecules as pathogens and pests-control agents. These may be profitably recovered in large amounts at the end of industrial milling processes. This is the case of the non-digestible hull of common buckwheat (Fagopyrum esculentum Moench), a natural source of polyphenols, tocopherols, phytosterols and fatty acids. We extract these compounds from the hull of buckwheat; apply them to Aspergillus flavus - aflatoxin producer - under in vitro conditions, checking their ability to inhibit fungal growth and aflatoxin biosynthesis. Moreover, a solvent free method implying the adoption of supercritical CO2 as solvent was set up to extract lipophilic molecules from the buckwheat’ hulls. Positive results in controlling fungal growth and aflatoxin biosynthesis let infer that the extracts could be further tested also under in vivo conditions